Evaluation of the CAPM Model in Estimating Sharia Stock Returns on the IDX Sharia Growth 2022–2024 - Ariq Ananta Wiguna (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study aims to evaluate the effectiveness of the Capital Asset Pricing Model (CAPM) in predicting the return rates of sharia stocks included in the IDX Sharia Growth Index for the period 2022–2024. The study uses a quantitative approach with purposive sampling techniques to select stocks that meet the eligibility criteria for analysis. The CAPM model was tested through linear regression against the difference between market returns and risk-free returns to obtain beta values and identify the systematic risk level of each stock. The results show that CAPM has strong predictive power in estimating the returns of sharia stocks on the index, as indicated by the significance of the beta coefficient and the fit of the regression model. Several stocks were also identified as efficient stocks because they were able to provide actual returns that were higher than the returns predicted by CAPM. These findings confirm that CAPM can be used as a relevant analytical tool for investors in determining investment strategies in the Islamic capital market in Indonesia.